Feminism, nationalism, and labour in post-civil war Northern Province of Sri Lanka - Sarvananthan, M.; Suresh, J.; Alagarajah, A. (DEVELOPMENT IN PRACTICE, 2017)
This viewpoint highlights the paradox of low labour force participation and high unemployment among women at a time of growing educational levels of women in the former conflict-affected Northern Province of Sri Lanka. It highlights the rise of ethno-feminism and sub-nationalism that undermine what few opportunities open up for women in terms of employment and livelihood opportunities, thereby weakening the peacebuilding efforts of various stakeholders. Ce point de vue met l’accent sur le paradoxe de la faible participation de la force active et du chômage élevé parmi les femmes, à un moment où les niveaux d’éducation chez les femmes sont de plus en plus élevés dans la province Nord du Sri Lanka, anciennement affectée par la guerre civile. Il souligne l’émergence de l’ethno-féminisme et du sous-nationalisme qui sapent les quelques opportunités offertes aux femmes en matière d’emploi et de moyens d’existence, affaiblissant ainsi les efforts de consolidation de la paix de divers intervenants. Este punto de vista resalta la paradoja resultante de la baja inserción de mujeres en la fuerza laboral y el alto desempleo femenino en un momento en que se ha elevado el nivel de escolaridad de las mismas en la Provincia Norte de Sri Lanka, anteriormente afectada por el conflicto. En este sentido, el artículo destaca el surgimiento del etnofeminismo y el subnacionalismo, que socavan las pocas oportunidades que se van dando para las mujeres en términos de empleo y de medios de vida, debilitando de esta forma los esfuerzos que varios actores realizan para construir la paz.
Keywords: Labour and livelihoods; Gender and diversity